1987
DOI: 10.1056/nejm198707303170503
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lupus Psychosis and Antiribosomal P Protein Antibodies

Abstract: In 18 of 20 patients with psychosis secondary to systemic lupus erythematosus (SLE), autoantibodies to ribosomal P proteins were detected by immunoblotting and measured with a new radioimmunoassay using a synthetic peptide as antigen. The frequency of anti-P was not increased in patients with other central nervous system manifestations of SLE (3 of 20, by radioimmunoassay), in patients with transient behavioral abnormalities due to SLE (none of 8), in patients with psychosis who did not have SLE (none of 13), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
293
4
24

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(332 citation statements)
references
References 33 publications
11
293
4
24
Order By: Relevance
“…It is therefore possible that anti-NR2 antibodies might also be produced within the CNS, leading to their elevation in CSF and to neuronal damage. In contrast, anti-ribosomal P (anti-P) antibodies in the serum have been shown to be associated with diffuse NPSLE (4,16,19). We have recently demonstrated that anti-P antibodies up-regulate the expression of tumor necrosis factor ␣ protein and messenger RNA in human peripheral blood monocytes (20).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that anti-NR2 antibodies might also be produced within the CNS, leading to their elevation in CSF and to neuronal damage. In contrast, anti-ribosomal P (anti-P) antibodies in the serum have been shown to be associated with diffuse NPSLE (4,16,19). We have recently demonstrated that anti-P antibodies up-regulate the expression of tumor necrosis factor ␣ protein and messenger RNA in human peripheral blood monocytes (20).…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal study published over 20 years ago, antiribosomal P autoantibodies were detected in 90% of patients with SLE and psychosis, 45 and recent work suggests that this antibody might cross-react with a neuronal surface protein to initiate calcium influx and apoptosis. 46 However, large clinical studies and meta-analyses have reached variable results with regard to the presence of antiribosomal P antibodies in neuropsychiatric SLE, with differences attributed to laboratory methodology, study population, fluctuating course of disease, and diagnostic discrepancies.…”
Section: Encephalopathy In Lupus and Other Systemic Syndromesmentioning
confidence: 99%
“…Accordingly, anti-P antibodies also up-regulated the expression of TNF␣ and IL-6 messenger RNA in activated monocytes. Of note, F(ab ) 2 …”
mentioning
confidence: 99%